PENGEMBANGAN APLIKASI MENGHAFAL AL-QUR’AN BERBASIS ANDROID - Herfandi; Fitria, Anggi (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2022)
Learning the Qur'an is an obligation for every believer. The process of memorizing the Qur'an uses a special memorization method that is different in each cottage, but the application of the method or method of memorizing cannot be used by general beginner memorizers, so it will make the memorization process hampered or feel heavy. Therefore, this study developed an application to assist believers in memorizing the Qur'an. Utilization of android-based smartphone applications can help and facilitate people who want to memorize the Qur'an. The research approach model used is qualitative with data collection techniques namely observation, interviews, literature study. While the software development model is the waterfall model. The results of this study are the Hafidz.id application for memorizing the Qur'an using android technology that can be accessed online and offline with audio features, verse text, images, translations and the addition of asbabun nuzul/stories that support Arabic text. There are two views, namely hafiz kids and formal, there is a memorization model that is applied per verse (one verse in one scene). This application has successfully passed the system testing process using black box testing and got successful results in all tests.